Hazard Assessment of Peanut Drought and Flood Disasters in Huang-Huai-Hai Region - Wei Sicheng; Li Kaiwei; Zhang Jiquan; Yang Yueting; Liu Cong; Wang Chunyi (应用气象学报)
Peanut is an important kind of food, oil plants and cash crops which promotes the sustainable development in the modern agricultural economy. In recent years, the frequency and intensity of drought disaster and waterlogging disaster in the Huang-Huai-Hai Region has remarkably increased, which poses a huge impact on the production of spring peanut. Therefore, analyzing and making hazard assessment of drought disaster and waterlogging disaster during the growth period of spring peanut has a great significance for preventing drought disaster and waterlogging disaster, minimizing the damage, and taking disaster insurance in this region. Based on the daily meteorological data of 186 meteorological stations from 1960 to 2019 and combined with the growth data of spring peanut, the hazard assessment of drought disaster and waterlogging disaster is divided into 7 grades by using the standardized precipitation requirement index(ISPR), and the spatial and temporary distribution characteristics of drought disaster and waterlogging disaster in Huang-Huai-Hai Region are analyzed. Based on the probability and intensity of drought disaster and waterlogging disaster, hazard index is constructed to evaluate the hazard during the growth period of spring peanut. High incidence of drought disaster is found in the northwestern and central part of the Yellow River Basin, the northeastern part of the Huaihe River Basin and the northern part of the Haihe River Basin. While the areas with high incidence of waterlogging disaster are mainly concentrated in most areas of the Yellow River Basin, the northern, southern part of the Huaihe River Basin and eastern part of the Haihe River Basin, and mainly with moderate waterlogging disaster. The areas with high hazard of drought disaster during the growth period of spring peanut are scattered, mainly concentrated in the northwest of the Yellow River Basin. While the areas with medium and high hazard of waterlogging disaster during the growth period of spring peanut are mainly distributed in the Yellow River Basin. In the northern and central planting areas of the Yellow River Basin, the phenomenon of drought disaster and waterlogging disaster abrupt alternation often occurs. Therefore, it is necessary to reduce the hazard of drought disaster and waterlogging disaster abrupt alternation, regulate crop exposure in planting areas, reduce the vulnerability of crop, improve the overall disaster prevention and mitigation capabilities, and promote management level in planting areas. The above research results can provide a reference for the drought disaster and waterlogging disaster prevention and loss reduction during the growth period of spring peanut and the construction of security production guarantee method system in Huang-Huai-Hai Region.